Effect of Acupressure with Cardamom Massage Oil on the Severity of Common Cold in Children Aged 3-5 Years - Lusi Ayuandita, Hera; Arwani, Arwani; Wahyuni, Sri (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2026)
Background: The common cold is one of the most common infectious diseases in toddlers and can reduce their comfort and activity. Non-pharmacological treatments, such as acupressure, are becoming increasingly popular because they are considered safe and can enhance the immune response. Cardamom massage oil contains bioactive compounds thought to help relieve symptoms and improve immune function. The purpose of this study was to determine the effectiveness of acupressure with cardamom oil on the severity of the common cold in toddlers aged 3-5 years, based on temperature and Immunoglobulin A (IgA) levels. Subjects and Methods: This study used a true experimental design and a pretest-posttest with a control group. The study was conducted at the Purwokerto Timur I Community Health Center in November 2025. A total of 32 subjects were divided into two groups: (1) The intervention group was given acupressure intervention group with cardamom oil for 30 minutes/day for 5 days (n = 16), and (2) The control group was given control group given Dextromethorphan, Pseudoephedrine, CTM, Paracetamol, and Vitamin C (n = 16). The dependent variables were body temperature and IgA levels. The independent variables were acupressure with cardamom oil and Dextromethorphan, Pseudoephedrine, CTM, Paracetamol, and Vitamin C. Body temperature is measured using a thermometer. IgA levels were measured using an ELISA kit. Data were analyzed by Paired t-tests. Results: The average body temperature in the intervention group after acupressure with cardamom oil was lower (Mean = 36.7; SD = 0.23) compared to before the intervention (Mean = 38.1; SD = 0.29) and was statistically significant (p <0.001). The average IgA levels in the intervention group after acupressure with cardamom oil were higher (Mean = 52.91; SD = 19.94) than before the intervention (Mean = 31.64; SD = 16.49) and were statistically significant (p<0.001). Conclusion: Acupressure with cardamom oil has been shown to be effective for the common cold by lowering body temperature and increasing IgA levels in toddlers aged 3-5 years.